Ethnobotany and Traditional Ecological Knowledge of Sugar Palm (Arenga Pinnata (Wurmb.) Merr.) in Pusuk Lestari Village, West Lombok, Indonesia - Angrenani, Aniska Arsitaningtyas; Sukenti, Kurniasih; Suana, I Wayan (International Journal Labs, 2026)
Sugar palm (Arenga pinnata (Wurmb.) Merr.) is a multipurpose non-timber forest product that plays important ecological, socio-cultural, and economic roles in rural communities of Indonesia. This study aims to document ethnobotanical knowledge, traditional ecological knowledge (TEK), and plant part utilization patterns of sugar palm in Pusuk Lestari Village, West Lombok, Indonesia. Data were collected using a mixed-method approach through semi-structured interviews, participant observation, and field documentation involving 23 key informants selected using snowball sampling. Quantitative analysis of plant part utilization was conducted using the Plant Part Value (PPV) index based on reported uses. The results indicate that the community utilizes six main plant organs of A. pinnata, namely roots, stems, leaves, inflorescences, fruits, and seeds. Leaves exhibited the highest PPV value (32.14%), followed by stems (28.57%) and inflorescences (21.43%), reflecting a preference for renewable and multifunctional plant organs. In contrast, roots and seeds showed the lowest PPV values, indicating limited use of vital plant organs. Traditional tapping practices are guided by TEK, including phenological indicators, ritual practices, taboos, and the use of natural anti-fermentation agents, which collectively support sap quality, safety, and continuity of production. Economically, sugar palm sap provides stable daily income, while other products such as ijuk (palm fiber derived from the fibrous sheath), young leaves, and kolang-kaling (immature sugar palm fruit) serve as supplementary and seasonal resources. Overall, the integration of ethnobotanical knowledge and PPV analysis indicates that A.